The Effect of Garlic (Allium sativum L) Supplementation on Production and Egg Cholesterol Level of Hysex Brown Laying Hens - Sutama, INS; Lindawati, SA (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2008)
This aims of this study was to evaluate the effect of garlic supplementation on production and egg cholesterol level of Hysex Brown laying hens. This study was conducted based on Completely Randomized Design with four treatment of garlic containing 0; 2; 4 and 6% and five replicate. In each replicate, there were four hens aged 38 weeks. The formulation diet of 2.900,01 ME kcal/kg, 16.5% of protein and drinking water were prepared in ad libitum during 4 weeks observation. The result showed that the effect of garlic supplementation 0, 2 and 6% respectively did not show any significant effect toward feed intake, egg production, egg cholesterol, egg weight, egg yolk and drinking water during 4 weeks of observation. It was found that 4% garlic supplementation significantly (P<0.05) reduced on egg cholesterol by 14.23% and did not affect the eggs production. It was concluded that garlic supplementation did not affect egg production, but garlic supplementation 4% decreased egg cholesterol of Hysex Brown laying hens. (Animal Production 10(3): 168-173 (2008) Key Words: Garlic, egg production, egg cholesterol, laying hens